Current trends of antimicrobial susceptibility of typhoidal salmonellae in adult population in a federal tertiary care hospital - Islamabad - Ali, Muhammad Moaaz; Farwa, Umme Farwa; Samia, Samia Wazir; Kaleem, Fatima; Tariq, Mariam; Abbasi, Shahid Ahmad (Infectious Diseases Journal of Pakistan, 2025)
Background: Salmonella typhi and Salmonella paratyphi A, B, and C are the primary causes of typhoid fever, which affects about 21 million people yearly and poses a serious health risk. Pakistan’s population is especially susceptible because of the disease’s high frequency. The increasing prevalence is made worse by Salmonella typhi types that are resistant to antibiotics, which emphasizes the need for thorough investigation and action. The purpose of this study was to evaluate the patterns of antibiotic susceptibility among typhoid patients. Material and Methods: This cross-sectional study was conducted in Islamabad from June 2021 to December 2022. Patients with healthy positive blood cultures, both male and female, were enrolled in the study. Susceptibility testing was performed on 110 samples of Salmonella typhi and 40 isolates of Salmonella paratyphi against seven antibiotics. Information was gathered in a tertiary hospital in Islamabad, Pakistan. Results: It is concerning to note that 47% of Salmonella typhi isolates showed extensive drug resistance (XDR), and 25% showed multidrug resistance (MDR). Interestingly, no MDR or XDR was seen in any of the isolates of Salmonella paratyphi. Conclusion: Urgent action is required to combat the growing threat of typhoid fever caused by antibiotic resistance. The study emphasizes the need to use antibiotics wisely and effectively. The results highlight the necessity of close monitoring and a diversified strategy to tackle the growing threat of drug-resistant Salmonella typhi. Keywords: Typhoid fever, Salmonella typhi, Salmonella paratyphi, Antibiotic resistance, Multidrug resistance, Azithromycin sensitivity, Healthcare challenges